A12 PRE-TREATMENT HLADQA1-HLADRB1 TESTING FOR THE PREVENTION OF AZATHIOPRINE-INDUCED PANCREATITIS IN INFLAMMATORY BOWEL DISEASE: A PROSPECTIVE COHORT STUDY. (4th March 2021) - Wilson, A; Wang, M; Ponich, T; Gregor, J C; Chande, N; Yan, B; Sey, M; Beaton, M D; Kim, R
Abstract: Background: Azathioprine (AZA) therapy has a long history of use in IBD. The need to promote its safe use in this population is ensured by governmental health policy requiring IBD patients to fail low cost drugs, such as AZA, prior to approving funding for more potent biologic therapies. AZA-induced pancreatitis is an idiosyncratic and unpredictable response, occurring in up to 7% of AZA-exposed patients that can lead to patient morbidity, hospitalization, delay in effective IBD management, as well as result in substantial additional health-related costs. There are no tools in clinical practice to identify individuals at risk of AZA-induced pancreatitis. Genetic variation in the HLADQA1-HLADRB1*07:01 haplotype is strongly associated with azathioprine (AZA)-induced pancreatitis in inflammatory bowel disease (IBD). Aims: To evaluate whether HLA DQA1-HLADRB1*07:01A>C pre-treatment genotype testing in an adult IBD population prior to AZA therapy to guide AZA selection would result in a lower incidence of AZA-induced pancreatitis. Methods: Participants with IBD (n=599) were screened for HLADQA1-HLADRB1*07:01A>C and participants with a variant genotype were excluded from azathioprine treatment (n=271). Wildtype participants (n=328) were started on azathioprine and followed for 3 months. The incidence of pancreatitis was compared to unscreened historical controls (n=373). Results: The minor allele frequency of HLADQA1-HLADRB1*07:01 was 30.4% and 30.0% in the screened and unscreened populations respectively. Up to 45.2% of participants were excluded from AZA therapy based on genotype in the HLADQA1-HLADRB1*07:01A>C screened cohort. HLADQA1-HLADRB1*07:01A>C screening resulted in an 11-fold reduction in the odds of azathioprine-induced pancreatitis (0.30% versus 3.4%, OR=0.085, 95%CI=0.011–0.651, p=0.002). Conclusions: HLA DQA1-HLADRB1*07:01A>C screening substantially reduced the risk of pancreatitis during AZA treatment in patients with IBD. However, using this strategy as a tool for guiding the use of AZA therapy in IBD may eliminate a large proportion of patients from being eligible for treatment with AZA. In regions, where there is access to other IBD therapies, and given the short and long term toxicities associated with AZA, HLA DQA1-HLADRB1*07:01A>C screening may be a clinically-relevant strategy for enhancing the safe use of AZA in IBD. Additionally, cost-effectiveness analyses are needed to further solidify the utility of HLA DQA1-HLADRB1*07:01A>C -screening in IBD populations. Funding Agencies: Academic Medical Organization of Southwestern Ontario Innovation Fund